Impact of Nutritional Status on the Quality of Life in Head and Neck Cancer Patients Undergoing Radiotherapy - Ujang, Noriati (2009)
Malnutrition is prevalent in head and neck cancer patients due to premorbid lifestyles, local effects of the tumor, and side-effects of the treatment. Malnutrition has been reported to have a negative impact on the quality of life of these patients while undergoing treatment. This study aims to determine the impact of nutritional status on quality of life of head and neck cancer patients undergoing radiotherapy (primary, adjunctive to surgery or combined with chemotherapy), as well as to identify the contributing factors to these parameters. A cross-sectional study was carried out in a convenience sample of 50 head and neck cancer patients receiving radiotherapy (primary, adjunctive to surgery or combined with chemotherapy) who were admitted to the oncology wards, Hospital Kuala Lumpur. Nutritional status was assessed objectively by using combination of anthropometry, biochemical and dietary method, and subjectively (using Patient-Generated Subjective Global Assessment or PG-SGA). Quality of life was evaluated by using the European Organization for Research and Treatment of Cancer Quality of Life Core Questionnaire (EORTC QLQ-C30 and its head and neck module (EORTC QLQ-H&N35). Of 50 patients, 58% (n=29) were found to be malnourished by using objective criteria, while 84% (n=42) were found to be malnourished by using subjective measure (PG-SGA). Poor quality of life was reported in 56% of the patients. None of the sociodemographic factors studied was associated with malnutrition. Bivariate analysis showed that two clinical variables (treatment type and radiation dosage) significantly affected nutritional status. Chemoradiated patients were found to be more malnourished than those treated with radiotherapy alone or post-operative radiotherapy (F= 7.832, p<0.05). Multivariate analysis revealed that neoadjuvant chemoradiation and post-operative radiotherapy significantly affected nutritional status (F = 12.085, p= 0.000, R2= 0.340). Both contributed 34% of the variance seen in the nutritional status of the patients. In terms of QoL, 56% of patients had poor QoL. Bivariate analysis showed that treatment modality and nutritional status were significantly associated with QoL. Post-operative radiotherapy was associated with better quality of life, followed by those treated with radiotherapy alone, neoadjuvant chemoradiation and concurrent chemoradiation (F= 6.721, p<0.05). As anticipated, malnourished patients had significantly poorer QoL (Mann- Whitney test = 66.5, p<0.05). However, multivariate analysis revealed that nutritional status was not a significant contributor of QoL. The only two significant contributors of QoL were household income and post-operative radiotherapy, and both explained about 40% of the variance seen in the QoL of the patients (F= 14.901, p = 0.000, R2 = 0.398). In short, the results of this study has highlighted that malnutrition was very prevalent in head and neck cancer patients. The findings also provide an insight into factors that contribute to both nutritional status and QoL. A longitudinal study is needed in order to determine the real effect of treatment over time in both nutritional status and QoL of the patients.